1976
DOI: 10.1902/jop.1976.47.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Freeze‐dried Bone Allografts in Periodontal Osseous Defects,

Abstract: Freeze-dried cortical bone allografts of a fine particle size were implanted into wide three-wall, two-wall, one-wall, combination, and furcation defects. Of the 97 defects treated, 23 manifested complete bone regeneration; 39 showed greater than 50%; and 24, less than 50% osseous repair. Twelve defects failed to demonstrate any bony regeneration, of which nine were furcation involvements. From the preliminary data available, there is strong evidence which indicates that freeze-dried bone allografts have defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 32 publications
2
60
1
1
Order By: Relevance
“…ABBM is an extensively researched material which has been successfully used alone for treatment of intra-bony and furcation defects, with a positive role in reducing PD, promoting CAL gain and enhancing defect fill in periodontal defects. 3,4,5,32 The positive results of the control group (ABBM alone) are in accordance with findings from previous studies which had failed to show significant differences between treatment with ABBM alone or combinations of ABBM with enamel matrix derivative or platelet-rich plasma (PRP). 30,39 Although the results of this study suggest that treatment with ABBM-PRF may not have provided significantly better results than those obtained with ABBM alone, the possibility for PRF to show any beneficial effects over the control group might have been masked by the fact that treatment with ABBM alone resulted in significant improvement.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…ABBM is an extensively researched material which has been successfully used alone for treatment of intra-bony and furcation defects, with a positive role in reducing PD, promoting CAL gain and enhancing defect fill in periodontal defects. 3,4,5,32 The positive results of the control group (ABBM alone) are in accordance with findings from previous studies which had failed to show significant differences between treatment with ABBM alone or combinations of ABBM with enamel matrix derivative or platelet-rich plasma (PRP). 30,39 Although the results of this study suggest that treatment with ABBM-PRF may not have provided significantly better results than those obtained with ABBM alone, the possibility for PRF to show any beneficial effects over the control group might have been masked by the fact that treatment with ABBM alone resulted in significant improvement.…”
supporting
confidence: 89%
“…2 Histologically, new bone, cementum and new periodontal ligament formation have been observed in periodontal defects treated with ABBM. 3,4 Considering its aforementioned properties, ABBM has been successfully used in regenerative treatment of intra-bony and furcation defects. 1,5 In recent years, researchers have focused on biological mediators which have the ability to enhance wound healing and improve clinical benefits of bone replacement grafts.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, in previous studies, it has been reported that FDBA and DFDBA type allograft were observed in new periodontal ligament, cement and alveolar bone formation as a percentage of 50-60% and 80 %, respectively. [25][26][27][28] Also, several studies suggested that allograft (Puros®) was superior than the other graft materials, and that it was almost as effective as autogenous graft.…”
Section: Discussionmentioning
confidence: 99%
“…For example, successful clinical outcomes using deproteinized cancellous bovine bone (DPBB) matrices (e.g., Bio-Oss ® ) have been reported in the treatment of periodontal and jaw bone defects [1][2][3][4][5] and in sinus lift procedures [6][7][8] . However, these allogeneic or xenogeneic bone grafts may transmit diseases and cause immune-related complications 9) .…”
Section: Introductionmentioning
confidence: 99%